The effect of monetary policies on the economy of the Western Balkan countries - Jelena Ignjatović; Aleksandra orević (Agora International Journal of Economical Sciences (AIJES), 2025)
Monetary policies have one of the key roles in the creation of economic policies of all countries of the world. Although the main task of monetary policy is to regulate the required amount of money, the objectives of monetary policy can have a development and stabilization character, which affects the entire economy of a country. In accordance with that, this paper analyzes development goals through economic growth and employment growth, as well as stabilization goals through price stability and balance of payments. The aim of this paper is to point out the effects of monetary policy on the economies of the Western Balkan countries, which have been striving for integration into the European Union for years. The research is based on a systematic review of theoretical frameworks and empirical verification of results. In addition to the introduction, the paper consists of three parts. The first part of the paper evaluates the monetary policies of the Western Balkan region over time, while the second part analyzes the development goals of these countries. The third part of the paper examines the stabilization goals of the countries of the Western Balkans. Finally, concluding remarks are given. The results of the research indicate that the monetary policies of the region are designed to be in line with the requirements of the EU, focusing on integration and socio-economic convergence with the EU. In addition, the Western Balkan countries record lower economic growth rates compared to the EU, while on the other hand they record significantly higher average inflation and unemployment, which is not in line with the goals of European integration in the future.
Keywords: 330; monetary policy; EU integration; Western Balkans countries